The Application of Seesaw in Improving Student Learning Activities - Antyesti; Tutut Handayani; Umiera Hashim, Haida (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
The purpose of this study is to ascertain how using the Seesaw application affects students' learning engagement in Islamic Religious Education courses. The low level of learning activity among eighth-grade students at SMP Muhammadiyah 3 Gunung Raja, Muara Enim Regency, serves as the backdrop for this study. Students are typically passive when it comes to asking questions, responding to them, and taking part in discussions. The study employs a Pre-Experimental One Group Pretest–Posttest Design and quantitative methodology. Purposive sampling was used to choose 35 eighth-grade students from class VIII A for the research sample. The data was gathered using a learning activity questionnaire with 25 statements on a four-point Likert scale. The Shapiro-Wilk normality test and paired sample t-test were employed in SPSS version 27 to evaluate the findings. Using a pretest average of 56.66 and a posttest mean of 83.8, as well as a t-value of 58.718 > t-table 2.032 (p < 0.05), the study's findings demonstrated a significant increase in students' learning activity following the deployment of Seesaw. In addition to promoting creative Islamic education learning in the digital age, the Seesaw application has been shown to be successful in raising students' motivation and learning activity.